Teacher Performance Analysis in Terms of Job Satisfaction and Commitment - Marsuhin Marsuhin; Zainul Hidayat (Innovation Business Management and Accounting Journal, 2022)
The problem of teacher performance is an important problem that must be addressed immediately. Factors The main cause in terms of lack of job satisfaction and commitment. This study aims to prove that job satisfaction and commitment have an effect either partially or simultaneously on performance. And to prove which of the job satisfaction and commitment have a dominant effect on the performance of teachers in SMA PGRI 1 Lumajang, East Java, Indonesia. This research uses multiple linear regression method and then the data results are processed with the help of the SPSS program and hypothesis testing. The results showed that job satisfaction and commitment to performance. The higher the job satisfaction, the higher the performance. Likewise with commitment, the higher the commitment to work, the higher the performance. The uniqueness of this research is the main supporting factor in improving performance, namely job satisfaction. In improving teacher performance, what must be considered is the teacher's job satisfaction factor.